Global research trends and hotspots on tendon-derived stem cell: a bibliometric visualization study - Zhang, Songou; Shang, Jinxiang; Gu, Zhiqian; Gu, Xiaopeng; Wang, Fei; Hu, Xujun; Wu, Guoliang; Zou, Huan; Ruan, Jian; He, Xinkun; Bao, Chenzhou; Zhang, ZhenYu; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
Purpose: This study was aimed to examine the global research status and current research hotspots in the field of tendon stem cells. Methods: Bibliometric methods were employed to retrieve relevant data from the Web of Science Core Collection (WOSCC) database. Additionally, Citespace, Vosviewer, SCImago, and Graphad Prism were utilized to analyze the publication status in this field, identify the current research hotspots, and present a mini-review. Results: The most active countries in this field were China and the United States. Notable authors contributing significantly to this research included Lui Pauline Po Yee, Tang Kanglai, Zhang Jianying, Yin Zi, and Chen Xiao, predominantly affiliated with institutions such as the Hong Kong Hospital Authority, Third Military Medical University, University of Pittsburgh, and Zhejiang University. The most commonly published journals in this field were Stem Cells International, Journal of Orthopedic Research, and Stem Cell Research and Therapy. Moreover, the current research hotspots primarily revolved around scaffolds, molecular mechanisms, and inflammation regulation. Conclusion: Tendon stem cells hold significant potential as seed cells for tendon tissue engineering and offer promising avenues for further research Scaffolds, molecular mechanisms and inflammation regulation are currently research hotspots in this field.